Aplicação do RAPD (Randomly Amplified Polymorphic dna) para tipagem molecular de amostras de Salmonella isoladas de diversas fontes da cidade de Aracaju-SE - Góis, Plácia Barreto Prata (2006)
The Salmonella infection is a relevant problem in the public health, being one of the most important causes of the world´s enteric pathologies, with 1,3 million ill people, resulting in 600 deaths/year. The Salmonella spp. transmission occurs especially through water consumption and contaminated food. The diagnosis is realized using biochemical, serologic, and molecular tests. The RAPD (Randomly Amplified Polymorphic DNA) test is able to detect the genetic variation present in the isolated Salmonella spp. samples, allowing a molecular typing. This research aimed at achieving molecular typing from Salmonella spp. samples isolated from various resources (oyster, chicken, potable water, blood, and human feces) utilizing the RAPD technique. 33 Salmonella spp. samples, that came from bacteria located at the Laboratório de Virologia Comparada-DMO/CCBS/UFS, and two standard samples were utilized. Six randomized primers were used from the Ready-To-Go System RAPD; the products amplified were submitted to an electrophoretic run in a 5% polyacrilamid gel, and silver dyed. The band standard observed was analyzed by the NTSYS program. After a computational analysis it was possible to discriminate the 35 Salmonella spp. samples, resulting in 35 RAPD individual and distinct patterns, showing that the samples are genetically diversed and that there is an ample genetic biodiversity in the circulating samples in Aracaju-SE. To the grouping the Salmonella spp. samples was observed the epidemiological relationship between human samples and chicken.